Quantifying Interprofessional Learning In Health Professional Programs: The University of Manitoba Experience - Grymonpre, Ruby; Dean, Heather; James, Maria; Wener, Pam; Ready, Elizabeth; MacDonald, Laura; Holmqvist, Maxine; Fricke, Moni (Canadian Journal of Higher Education, 2017)
Internationally, a growing number of interprofessional education (IPE) offices are being established within academic institutions. However, few are applying educational improvement methodologies to evaluate and improve the interprofessional (IP) learning opportunities offered. The University of Manitoba IPE Initiative was established in 2008 to facilitate the development of IP learning opportunities for pre-licensure learners. The research question for this secondary analysis was: what, if any, changes in the number and attributes of IP learning opportunities occurred in the academic year 2008–2009 compared to 2011–2012? The Points for Interprofessional Scoring (PIPES) tool was used to quantify the attributes of each IP learning opportunity. Most notably in 2012, eight (73%) of 11 IP learning opportunities achieved the highest PIPES score (> 55), compared to only four (36%) in 2009. The concept of the PIPES score is introduced as an educational improvement strategy and a potential predictor of achieving the desired educational outcome: collaborative competence.